Uji aktivitas antihiperglikemia ekstrak batang Uncaria gambir (W.Hunter) Roxb. pada tikus diabetes - Alexandra, Francisca Diana; Frethernety, Agnes; Amiani, Winney; Aprelea, Reza Nathasya (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
This study aimed to prove the antihyperglycemic activity of the ethanol extract of bajakah Tampala stem (Uncaria gambir (W.Hunter) Roxb.) in rats induced by streptozotocin. The research was conducted experimentally using a true experiment posttest-only control group design. bajakah Tampala extract was extracted by maceration method using 96% ethanol solvent. The extract was made at 50mg/kgBB, 75mg/KgBB, and 100mg/KgBB in diabetic rats. The decrease in blood glucose levels of the negative control (27.27%) in this treatment was lower than that of glibenclamide (35.12%). The most significant decrease in blood glucose levels was achieved by 100 mg/kg BW, which was 44.85%. The treatment of Bajakah ethanol extract at various dose levels at the end of the observation showed a decrease in blood glucose levels but was not significantly different (p > 0.05). The results of this study did not show a significantly different decrease in blood glucose levels.